Budgeting practice in Singapore - an exploratory study using a survey / Tan Boon Seng and Low Kin Yew - Tan, Boon Seng; Low, Kin Yew (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2017)
This study is conducted to better understand budgeting practice in Singapore which may be critical for increasing competitiveness and productivity for firms, and increasing value-add contribution for accountants. We obtained 356 valid responses from an online survey administered to members of a professional accounting organization. We found that most firms prepare budget and many (about 30%) incorporate significant strategy assumptions in budgets. The time spend on budgeting (10%-20%) is lower than what was reported in US studies, and more time is spent in preparing than using the budget. Budgeting problems (e.g. ratcheting and sandbagging behaviour) are well recognized, but firms preparing budgets with business plans generally deem pros for budgeting exceeding cons. Firms with annual revenue below $1m prepare budget primarily for forecasting cash flows; larger firms focus more on guiding and coordinating business activities, with increasing importance on variance analysis as firm size increases. For firms that prepare budgets with business plans, employee compensation based on budget performance is not as prevalent as expected. About 70% of the firms set budget targets to monitor strategy execution, about 50% set budget target for employee performance evaluation, and about 43% compensate by budget performance. The implications of these findings are discussed.